(3ebOeI aj fXQjI GdeMGSHI (B/s - (3GdfbjH, ceGd YHO GdYRjRs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2004)
(3fTCI GdeMGSHI hJWhQ GdacQ GdeMGSHj(B- (3GdEWGQ GdfXQj hGdJWHjbj dYde GdeMGSHI(B- (3GdYfGUQ GdacQjI dYde GdeMGSHI(B- (3ehbY Yde GdeMGSHI GdeGdjI Vef GWGQ GdeYQaI(B- (3GdeMGSHI cfXGe ddeYdheGJ(B- (3GdhXGFa GdeYGUQI ddeMGSHI(B- (3efGgL GdHMK GdYdej hGdeMGSHj hJWhQ fXQjI GdeMGSHI(B- (3ebOeI aj eMGSHI GdJVNe(B.s
(3GdeQGLY U(B.463s
Keywords: (3GdeMGSHIs; (3fXQjGJ GdeMGSHIs